The Influence of Innovation and Transformational Leadership as a Mediator of Internal Control Systems on the Performance of Public Sector Organizations - Ali Musana; Agustinus Setyawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Abstract In the context of globalization and economic transformation, countries, including Indonesia, are striving to improve the performance of their public sector organizations. This article reviews the significant improvement in the efficiency and performance index of the Indonesian government according to the World Bank. However, some regional governments, such as Batam City, face difficulties in achieving the set performance targets. In-depth research is needed to identify the factors that influence such performance improvements. The Batam City government has sought to improve performance through strengthening internal control, innovation, and transformational leadership. However, the results have not reached their maximum potential. This article suggests further research on the relationship between Internal Control Systems (ICS), Innovation, Transformational Leaadership (TL) and Organizational Performance (OP) in the Indonesian public sector. The research also explores to what extent innovation can mediate the relationship between ICS and organizational performance, as well as how transformational leadership affects such mediation. City governments and other public sector organizations can use these findings as benchmarks and guidelines in an effort to advance their performance in the face of the demands of modernization and global competitiveness.